المشاركة السياسية وأثرها في تنمية قيم المواطنة - المحمد, محمود; ابراهيم, بانة (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
تتضح العلاقة ما بين المواطنة و عملية المشاركة بأنها وظيفية، حيث تؤدي ممارسة المشاركة السياسية وظيفة هامة بتجسيدها لمضمون المواطنة شكلاً ومضموناً، ونقلها من حيز الأفكار النظرية والقوانين إلى حيز التطبيق في الواقع المجتمعي، كما تفسح المواطنة بما تمنحه من حقوق وواجبات المجال أمام الفرد ليمارس مشاركته السياسية. ولذلك فإن إيجاد علاقة ايجابية بين المواطن والدولة، تتضمن قدراً عالياً من ممارسة المشاركة السياسية، ويحتاج استثمار هذه العلاقة لتفعيل مشاركة المواطنين السياسية في وطنهم، خاصة في ظل المتغيرات الثقافية والسياسية والاقتصادية و التكنولوجية التي عبر من خلالها المواطن حدود وطنه، وفي ظل المعوقات الموضوعية في واقعها المجتمعي. تعتبر المشاركة السياسية محدداً لا يستهان به من خلال ممارستها أو عدم ممارستها في تحجيم أو تعزيز وتنمية الشعور بالمواطنة، بما تنطوي عليه المواطنة من قيم الانتماء، والقانون، والولاء، والنظام، المسؤولية ، التزام، عدالة..وغيرها الكثير . يتناول البحث و أثر المشاركة السياسية في تنمية قيم المواطنة، خاصة(المسؤولية، الانتماء، النظام، والمشاركة كقيمة)، و بينت النتائج الدراسة أن أثر المشاركة على المواطنة بالمستوى النظري والوجداني أعلى من أثر المشاركة على المستوى السلوكي والتطبيقي، وهذا يتفق مع حال ضعف المشاركة السياسية التي تعاني منها سورية والمجتمعات العربية عامة كما بينت الأبحاث والدراسات. The relationship between citizenship and participation is clearly a functional one, where the exercise of political participation serves an important function. It embodies the content of citizenship in form and substance, and transfers it from theoretical ideas and laws into applications in community. Citizenship, which grantees rights and duties, gives the way for an individual to exercise his political participation. Therefore, finding a positive relationship between the citizen and the state includes a high level of exercising political participation which needs to be invested through activating the citizens’ political participation, especially in the light of cultural, political, economic and technological variables, which through it the citizen crosses the borders of his homeland, and under the objectivity obstacles in the reality of its community. Therefore, the political participation is considered a very important determinant by its exercising or non-exercising in sizing, strengthening and developing the sense of citizenship, including the inherent values of belonging, law, loyalty, order, responsibility, and many other values. The research is investigating the impact of political participation in developing citizenship values, especially (responsibility, belonging, law and the participation as a value). The study results shows the effect of participating on citizenship, in both theoretical and sentimental levels which is higher than the impact of participation on the behavioral and applied levels that is consistent with the case of the lack of political participation that Syria suffered from and the Arab societies in general